Hanggang dito na lamang at maraming salamat the movie - Tañada, Felino; Nadres, Orlando (Viva Video, Inc., 2007)
Fidel is a "closet" gay and Julie is a flaming "queen," but they are bosom buddies. Fidel has been paying for the education of young Efren, but is unable to confess his love for him--until events conspire for him to do so, with painful consequences.